2012
DOI: 10.1088/0004-637x/761/2/186
|View full text |Cite
|
Sign up to set email alerts
|

The H I Environment of the M101 Group

Abstract: We present a wide (8.5 • × 6.7 • , 1050 × 825 kpc), deep (σ NHI = 10 16.8−17.5 cm −2 ) neutral hydrogen (HI) map of the M101 galaxy group. We identify two new HI sources in the group environment, one an extremely low surface brightness (and hitherto unknown) dwarf galaxy, and the other a starless HI cloud, possibly primordial in origin. Our data show that M101's extended HI envelope takes the form of a ∼ 100 kpc long tidal loop or plume of HI extending to the southwest of the galaxy. The plume has an HI mass ∼… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 63 publications
4
83
1
Order By: Relevance
“…This means that the velocity field only crudely represents the overall kinematics. The heliocentric systemic velocity was found to be V sys = 208 ± 5 km s −1 , consistent with the value of 210 km s −1 found by Mihos et al (2012). 5 km s −1 are detected, even though the spectral resolution would allow detecting dispersions as low at 1.5 km s −1 .…”
Section: Datasupporting
confidence: 84%
See 1 more Smart Citation
“…This means that the velocity field only crudely represents the overall kinematics. The heliocentric systemic velocity was found to be V sys = 208 ± 5 km s −1 , consistent with the value of 210 km s −1 found by Mihos et al (2012). 5 km s −1 are detected, even though the spectral resolution would allow detecting dispersions as low at 1.5 km s −1 .…”
Section: Datasupporting
confidence: 84%
“…It has no optical counterpart, even in very deep optical images (Mihos et al 2012(Mihos et al , 2013. The immediate question is, of course, whether the object is a dark galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The results on NGC 6754 were later confirmed by Sánchez-Menguiano et al (2016a) by analysing the azimuthal abundance distribution of the galaxy. However, regarding M 101, a previous study performed by Li et al (2013) only observed marginal local metallicity inhomogeneities that the authors suggested may be linked to tidal features reported at that time (Mihos et al 2012). …”
Section: Dispersion Of the Gradient And Mixing Scalelengthmentioning
confidence: 82%
“…(Mihos et al 2012), the field strengths will have dropped to about 0.3 μG and 0.2 μG, respectively. Hence, the intragroup magnetic field strength is probably smaller than 0.3 μG, which is similar to the value estimated for a local group of irregular dwarf galaxies (Chyży et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…These maps show a complicated structure of many narrow, patchy spiral arms with large variations in pitch angle. The many linear arm segments and the asymmetry of the large-scale structure are attributed to a collision with the satellite galaxy NGC 5474 (Waller et al 1997;Kamphuis 1993;Mihos et al 2012). Kenney et al (1991) detected a bar in the centre in CO, which is also seen in Hα and near-infrared (NIR), but density waves are weak in M 101 (Kamphuis 1993).…”
Section: Introductionmentioning
confidence: 99%